FEATURES OF AGE CATEGORY OF THE BEGINNING OF 20th CENTURY - Svetlana Stezhko (Lìteraturnij Proces: Metodologìâ, Ìmena, Tendencìï)
The article analyses propaganda plays which create a broad basis for further consolidation in the mass consciousness of ideological concepts , mythologues, and behavioral stereotypes, wholly corresponding to the so-called social order of power and society. One of the most powerful ideological plots and cliches in plays-agitation is the conceptial plot contrasting «past — future» («old world / order / custom — a new world / order / custom»). The plot lines of the propaganda play, in fact, «appropriate» folklore subjects and fragments of the national historical narrative and rewrite them in accordance with the class-social ideology of the era. Theatricalization of history, as well as theatricalization of life, is carried out using ideological cliches, but based on historical stories. In the vast majority of cases, it is not about the use of plot conflicts from the biographies of historical figures, but on the contrary — about the rebirth of the plot schemes of folk historical songs, ballads, legends, and translations. The plot lines of the propaganda plays “take credit” for folk stories and fragments of the national historical narrative and transcribe it according to the class-social ideological settings of the era. This makes it possible to create a common historical memory. Due to this memory the national heroic pathos of the Ukrainian past is replaced by the images and metaphors of the class struggle of the proletariat and the peasantry. This image is wholly opposite to the national-patriotic, partly the existential-philosophical conception of the past, created in the late 19th and early 20th centuries in the dramatic works of Liudmyla Starytska-Cherniakhivska, Spyrydon Cherkasenko, Hnat Hotkevych, Mykhailo Hrushevskyi, Bohdan Lepky, Ivan Nechui-Levytskyi and other Ukrainian writers. National pride motive is replaced by the idea of “Soviet patriotism”, in order for “Ukrainians could celebrate their past, as long as it complemented, but did not combat with Russian imperial history” as S. Yekelchik notes.